IMPLEMENTASI ETIKA PROFESI SATUAN BRIGADE MOBIL KEPOLISIAN DAERAH JAWA TENGAH SEBAGAI PELAKSANA ESEKUSI PIDANA MATI (Lex Jurnalica, 2022)
AbstractThe implementation of the death penalty in Indonesia is carried out by a firing squad from the Brimob of the Indonesian National Police which is formed by the Head of the Regional Police in the jurisdiction of the court that imposes the death penalty. Among law enforcers, the police can be called the foremost law enforcer, strategic and decisive in the implementation of the criminal justice system (criminal justice system). The Satbrimob of the State Police of the Republic of Indonesia, which is the only implementer of the death penalty in Indonesia, must of course carry out its profession in accordance with the ethics of the existing legal profession, both juridically and sociologically. The purpose of this study was to analyze and determine the implementation of the legal profession of the Central Java Regional Police Satbrimob in the implementation of the death penalty which has actually been written in the legislation. The type of research used is empirical legal research with a qualitative approach. In carrying out their profession, members of the Central Java Regional Police Satbrimob are essentially in accordance with the work philosophy of the quiscan vigil. This philosophy means that the police work around the clock so that people can carry out their activities comfortably. The Satbrimkob of the Central Java Regional Police should not be limited to being the implementing agency, in this case there must be intense coordination with other implementing agencies in order to ensure public trust. Keywords: Brimob, Ethics of the legal profession, Death penalty. AbstrakPelaksanaan pidana mati di Indonesia dilaksanakan oleh regu penembak dari Brimob Kepolisian Negara Republik Indonesia yang dibentuk oleh Kepala Kepolisian Daerah pada wilayah hukum pengadilan yang menjatuhkan pidana mati. Diantara penegak hukum, polisi dapat disebut sebagai penegak hukum paling depan, startegis dan menentukan dalam implementasi sistem peradilan pidana (criminal justice system). Satbrimob Kepolisian Negara Republik Indonesia yang merupakan satu-satunya pelaksana pidana mati di Indonesia tentu harus menjalankan profesinya sesuai dengan etika profesi hukum yang ada baik secara yuridis maupun sosiologis. Tujuan penelitian ini adalah menganalisis dan mengetahui implementasi etika profesi hukum Satbrimob Kepolisian Daerah Jawa Tengah dalam pelaksanaan pidana mati yang sebenarnya sudah tertulis dalam peraturan perundang-undangan. Jenis penelitian yang digunakan adalah penelitian hukum empris dengan pendekatan kualitatif. Dalam menjalankan profesinya, para anggota Satbrimob Kepolisian Daerah Jawa Tengah pada hakikatnya telah sesuai dengan filosofi kerja vigilat quiscant. Filosofi tersebut memiliki arti polisi melakukan pekerjaannya sepanjang masa agar masyarakat dapat menjalankan aktivitasnya dengan nyaman. Satbrimkob Kepolisian Daerah Jawa Tengah seharusnya tidak hanya sebatas sebagai instansi pelaksana, dalam hal ini harus terjadi koordinasi yang intens dengan instansi-instansi pelaksana lainnya agar menjamin kepercayaan masyarakat. Kata kunci: Brimob, Etika profesi hukum, pidana mati.